Implementation of Total Quality Management (TQM): Optimizing School Branding Strategy in Urban Islamic Schools - Hendra Kurniawan; Syamsul Arifin; Mulyono Mulyono (AL-ISHLAH: Jurnal Pendidikan, 2024)
Islam Terpadu Schools and Islam Unggulan Schools have emerged as alternative educational models combining Islamic and modern education. These institutions aim to strengthen religious foundations, build character, and enhance digital capabilities, addressing contemporary educational challenges. This qualitative study examines the school branding strategies of Islam Terpadu High School Al Fityan and Islam High School Al Amjad in Medan. Data collection methods included observations, interviews, and document analysis, involving key stakeholders such as school foundations, administrators, students, the community, and the JSIT (Jaringan Sekolah Islam Terpadu) network in North Sumatra. The analysis integrates Total Quality Management principles to contextualize branding efforts. Al Fityan High School employs the "Islam Terpadu" label to target upper-middle-class Muslim families, emphasizing extracurricular activities, character development, and a boarding school system. It differentiates itself through strategic use of social media for mass publication of school activities. Similarly, Al Amjad High School uses the "Islamic" label to position itself as a leading urban religious school. Its strategies include Quranic learning using the WAFA method, comprehensive teacher training, integrative learning, and guidance for college admissions. Both schools leverage brand image strategies to enhance their appeal and societal impact. These branding strategies contribute to increased community demand, positively influencing societal perceptions and graduate employability. Future research could explore the long-term effects of these strategies on student outcomes and community development. Effective branding strategies in Islamic education can enhance institutional reputation, community impact, and graduate success, positioning these schools as models for integrating religious and modern education.